2015
DOI: 10.1371/journal.pone.0135430
|View full text |Cite
|
Sign up to set email alerts
|

High Resolution Consensus Mapping of Quantitative Trait Loci for Fiber Strength, Length and Micronaire on Chromosome 25 of the Upland Cotton (Gossypium hirsutum L.)

Abstract: Cotton (Gossypium hirsutum L.) is an important agricultural crop that provides renewable natural fiber resources for the global textile industry. Technological developments in the textile industry and improvements in human living standards have increased the requirement for supplies and better quality cotton. Upland cotton 0–153 is an elite cultivar harboring strong fiber strength genes. To conduct quantitative trait locus (QTL) mapping for fiber quality in 0–153, we developed a population of 196 recombinant i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 49 publications
5
39
0
Order By: Relevance
“…Additionally, qFS-c7 was also verified in F 2 and RIL populations [46]. qFS-c13-1 and qFS-c13-2 were detected in an RIL population [44] and a natural population [47], respectively. The stable QTL qFE-c22 was also confirmed as qELO-c22 in the previous study [45].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Additionally, qFS-c7 was also verified in F 2 and RIL populations [46]. qFS-c13-1 and qFS-c13-2 were detected in an RIL population [44] and a natural population [47], respectively. The stable QTL qFE-c22 was also confirmed as qELO-c22 in the previous study [45].…”
Section: Discussionmentioning
confidence: 98%
“…qFL-c10-2 was identified as a stable QTL in two studies [23,25]. qFL-c25 was detected as the major QTL qFL-C25-2 in a RIL population [44]. qFU-c22 was the same as the QTL qUI-c22 in a randomly mated recombinant inbred population [45].…”
Section: Discussionmentioning
confidence: 99%
“…The detail information about the population construction was described in Sun’s report [39]. The fiber quality of the parents and the line 69307 was described in Zhang’s report [40]. In the day of flowering, flower buds were tagged as zero DPA.…”
Section: Methodsmentioning
confidence: 99%
“…It is mainly determined by the secondary cell wall formation stage which affect the yield and quality of fiber, and are important for cotton because of its applications in agriculture. Genetic screens have identified a number of genes involved in fiber development [9]; however, the genes and molecular regulatory mechanisms governing the fiber developmental process and fiber strength are still little understood. In this study, we systematically identified and analyzed cotton fiber strength During recent years, significant progress has been made in large-scale genomic studies, revealing cotton fiber development involved genes and signaling pathways [12,15,20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Rapid and dynamic changes in genes during this stage have been revealed with a complex involving processes such as transcriptional regulation, signal transduction and metabolic pathways, may contribute to cotton fiber development [7,8]. Fiber strength is a multigenic trait controlled by number of genes [9]. A few genes involved in secondary cell wall and fiber strength have been identified.…”
Section: Introductionmentioning
confidence: 99%